Russia’s Invasion of Ukraine, the Driving Forces, and Implications for Africa - Osondu-Oti, Adaora; Iloh, Emeka C.; Omole, Oluwakemi (Journal of Contemporary International Relations and Diplomacy, 2022)
The study interrogates the issues surrounding Russia’s invasion of Ukraine and the ongoing war between the two Eastern European countries. It examines the remote and immediate causes of the invasion as well as the position of leading and other members of the UN Security Council and other world leaders on the aggression. The study also analysed Russia’s justification of the invasion based on the fact that Russia’s security is being threatened by the continued expansion of NATO to Eastern Europe, against which Moscow claims it is a red line that cannot be tolerated. A brief background of the crisis that led to the invasion/war was examined, as well as the internal and external factors that triggered the invasion. Finally, the paper examined the implications of Russia’s invasion of Africa. The study relied on documentary evidence sourced mainly from the internet and applied the realist theory in analysing the issues. The study found that though NATO’s expansion eastwards and Ukraine’s intention to join the security alliance were the immediate triggers for the invasion, several other remote factors contributed to the invasion. The study also found that though Africa is miles away from the theatre of conflict, it is being affected in several ways by the conflict. Amongst others, the paper recommends that Africa should maintain its non-aligned posture in the conflict, and should seek closer ties within the continent and with non-European partners to cushion the effects of the war.